2010
DOI: 10.2133/dmpk.dmpk-10-nt-057
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity Enhances GABA Uptake by Cultured Rat Retinal Capillary Endothelial Cells

Abstract: We have reported previously that taurine transporter (TauT) mediates γ-aminobutyric acid (GABA) as a substrate in a conditionally immortalized rat retinal capillary endothelial cell line (TR-iBRB2 cells). This study investigates how TauT-mediated GABA transport is regulated in TR-iBRB2 cells under hypertonic conditions. [³H]GABA uptake by TR-iBRB2 cells exposed to 12 h- to 24 h-hypertonic culture medium was significantly greater than that of isotonic culture medium. [³H]GABA uptake by TR-iBRB2 cells was Na(+)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…TAUT also mediates transport of β-alanine and gamma-aminobutyric acid (GABA) (Tomi et al 2008;Usui et al 2013). Hyperosmolar conditions could stimulate activity of TAUT, leading to increase in V max of taurine without affecting K m (El-Sherbeny et al 2004;Yahara et al 2010). Both in vivo and in vitro data demonstrated that taurine itself enhanced expression of retinal TAUT (Zeng et al 2010).…”
Section: Taurine Transporter (Taut/slc6a6)mentioning
confidence: 99%
“…TAUT also mediates transport of β-alanine and gamma-aminobutyric acid (GABA) (Tomi et al 2008;Usui et al 2013). Hyperosmolar conditions could stimulate activity of TAUT, leading to increase in V max of taurine without affecting K m (El-Sherbeny et al 2004;Yahara et al 2010). Both in vivo and in vitro data demonstrated that taurine itself enhanced expression of retinal TAUT (Zeng et al 2010).…”
Section: Taurine Transporter (Taut/slc6a6)mentioning
confidence: 99%